PENGARUH STRES KERJA DAN MOTIVASI KERJA TERHADAP SEMANGAT KERJA KARYAWAN DI THE BENE HOTEL KUTA BALI - I Ketut Gusadi Pranata; Ni Luh Sili Antari; NLK Julyanti Paramitha Sari (Journal Research of Management, 2022)
This study aims to analyze and prove the effect of work stress and work motivation on employee morale. Research is a correlational research, which is research that seeks to see whether two or more variables have a relationship or not, as well as the direction of the relationship. The sampling technique uses saturated sampling technique by using all members of the population as a sample. The number of respondents used is 71 employees of The Bene Hotel Kuta Bali. Multiple linear regression analysis using SPSS software version 23. The regression equation obtained is: Y = 16.054 - 0.186X1 + 0.143X2 + ɛ. The results of this study indicate that; 1) job stress has a negative and significant effect on employee morale, 2) work motivation has a positive and significant effect on employee morale, 4) job stress and work motivation has an effect of 29.3% on employee morale. Some suggestions that can be conveyed in this study are adjusting job descriptions and job specifications in order to avoid employee work stress, increase direct and indirect motivation and need further research with other variables not examined in this study.